Think like a dog [videorecording (DVD)] - Junger, Gil; Bateman, Gabriel, 2004-; Nayyar, Kunal; Jones, Julia, 1981-; Montgomery, Janet, 1985-; Fox, Megan, 1986-; Duhamel, Josh, 1972- (Lionsgate, 2020)
A 12-year-old tech prodigy's science experiment goes awry and he forges a telepathic connection with his best friend, his dog. The duo join forces and use their unique perspectives on life to comically overcome complications of family and school.